Nível de atividade física e qualidade de vida em aposentados residentes no município de Rio Claro - SP - Micali, Pollyanna Natalia [UNESP] (2015)
Some studies indicate that work leave and the retirement process represent significant losses in the people’s social life, though, it may mean the opportunity to project their life again. There are some speculations about the impact of the retirement on the level of physical activity (LPA) and quality of life (QL), however, there are many gaps to be covered in the literature. Objective: Analyze the influence of the retirement on the LPA and the possible relations with QL of retired people who live in Rio Claro-SP. Methods: The research was made in two moments. In the first moment, it was analyzed a survey database conducted in 2008 (n=1588) participants. In the second phase, it was attempted to find all participants from 2008 in order to invite them to contribute with the new stage of the survey. Among the invitations accepted, 706 took part of the research. The retirement effects were analyzed through a questionnaire validated for such a purpose, being: The International Physical Activity Questionnaire (IPAQ), Item short-form health survey 36 (SF-36), Questionnaire of Barriers to Physical Activity Practice (QBPAFI), Criteria Questionnaire of Brazilian Economic Classification (ABEP) and Questionnaire about retirement/disease (QAPD). The data was analyzed by descriptive analyses (average, percentage), afterwards, it was made by comparison analysis (Kruskall Wallis; chi-square) and association (Spearman Correlation; Cluster’s Analysis). The statistical program used for analyses was the SAS - with significance of p<0.05. Results: Participants who retired before 2008 showed lower LPA when compared with non retired people. The results also revealed lower QL for retired people in category “functional capacity” and “social aspects”. Regarding the paired analysis, there was a significant drop in LPA for people that retired between 2008 and 2014 (1209,26 – 379,193 minutes/week). The same for QL on category “functional capacity” (85,69 - 65,422 points). According to the results, it was conclude that retired people showed worse conditions when compared to non-retired people and paired participants. Also there was a significant drop in these variables, showing that there is an influence of retirement on LPA and QL, also on retirement period. Final Considerations: This way, retirement preparation programs and physical activities for retired people should be encourage and implemented in companies and institutes, with public health support in order to minimize theses effects.